2019
DOI: 10.1039/c9ra06172j
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor activity of 4,4′-bipyridinium amphiphiles

Abstract: The cell growth inhibition and apoptosis induction of 4,4′-bipyridinium amphiphiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that CO 2 production is an important parameter for the growth, metabolism and reproduction of microbes in contaminated soils. 41,42 The characterization of the petroleum-degrading bacteria diversity could indicate the variability of the microbe abundance during the soil remediation, and also access the condition of microbial degradation in petroleum hydrocarbon pollutant. As shown in Fig.…”
Section: Microbial Respiration and Petroleum-degrading Bacteria Divermentioning
confidence: 99%
“…Previous studies have reported that CO 2 production is an important parameter for the growth, metabolism and reproduction of microbes in contaminated soils. 41,42 The characterization of the petroleum-degrading bacteria diversity could indicate the variability of the microbe abundance during the soil remediation, and also access the condition of microbial degradation in petroleum hydrocarbon pollutant. As shown in Fig.…”
Section: Microbial Respiration and Petroleum-degrading Bacteria Divermentioning
confidence: 99%
“…In terms of pharmacological properties, the 4,4’‐bipyridyl system was used to prepare the supramolecular dimetallic trans ‐(Pt(II)(salicylaldimine)) 2 (4,4’‐bipyridine) 2BF 4 complex which showed in vitro anticancer effect comparable to cisplatin in breast (MCF‐7) and liver (HepG2) cancer cells [32] . Moreover, anticancer activity was reported for a series of 4,4’‐bipyridinium amphiphiles that, in vitro , showed IC 50 values in the low‐micromolar range against human cancer cells and the cisplatin resistant A549 cancer cells [33] …”
Section: Resultsmentioning
confidence: 99%
“…[32] Moreover, anticancer activity was reported for a series of 4,4'-bipyridinium amphiphiles that, in vitro, showed IC 50 values in the lowmicromolar range against human cancer cells and the cisplatin resistant A549 cancer cells. [33] Another interesting feature of substituted 4,4'-bipyridines is the possibility to introduce chirality in their structure. In this regard, compounds 2-6 are chiral for atropisomerism, namely for restricted rotation around the 4,4'-bond (chiral axis), whereas compounds 1 and 7 feature C 2 symmetry and are not chiral.…”
Section: Iodinated 44'-bipyridines As Potential Anticancer Agentsmentioning
confidence: 99%
“…In solution, compounds bearing one bipyridinium moiety show IC 50 values in cancerous cells ranging from 5.6 to 240 μM, some of them showing even higher cytotoxicity than cisplatin (IC 50 15–142 μM). Thus, the equivalent concentrations of compounds 1 – 3 conjugated on the particles were estimated as if they were in solution (see Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…Upon oxidation, superoxide radical anion is formed and transformed into other oxygen radicals, which attack unsaturated lipids of the cell membrane triggering lipid peroxidation, a radical chain reaction that eventually induces increased membrane fluidity, membrane integrity loss, and cell death. Although this toxicity is also nonselective for cancerous cells, it could be revisited for biomedical purposes such as the treatment of cancer, as it is independent of nucleus internalization, making it more efficient than other chemotherapeutic drugs. The cytotoxic potential of bipyridinium on cancerous cells has been studied in solution, observing that the length of the alkyl chain substituents has an important influence on their cytotoxicity; nonetheless, strategies for focalizing their cytotoxic effects still need to be found. Bipyridinium-derived compounds have been conjugated onto nanoparticles, mainly for electrochemical sensing, , or as gatekeepers of drug-loaded systems, , but not for this purpose.…”
mentioning
confidence: 99%